Cost, healthcare utilization, and outcomes of antibody-mediated rejection in kidney transplant recipients in the US. (1st January 2021) - Hart, Allyson; Zaun, David; Itzler, Robbin; Schladt, David; Israni, Ajay; Kasiske, Bertram
Abstract: Background: Antibody-mediated rejection (AMR) is one of the leading causes of graft loss in kidney transplant recipients but little is known about the associated cost and healthcare burden of AMR. Methods: We developed an algorithm to detect AMR using the 2006–2011 Centers for Medicare & Medicaid Services (CMS) using ICD-10 and billing codes as there is no specific ICD-10 or procedure code for AMR. We then compared healthcare utilization, cost, and risk of graft failure or death in AMR. patients versus matched controls. Results: The algorithm had a 39.4% true-positive rate (69/175) and a 4.1% false-positive rate (110/2, 655). We identified 5, 679/101, 554 (5.6%) with AMR, who had a nearly 3-fold higher risk of graft failure (hazard ratio [HR], 2.75, 95% confidence interval [CI], 2.50 to 3.03; p < .0001) and death (HR, 2.59; 95% CI, 2.35 to 2.86; p < .0001) at 2 years, nearly 5 times the hospitalizations in the 60 d before AMR diagnosis, and increased nephrology and emergency department visits. Mean AMR attributable healthcare costs were 4 times higher than matched controls, at 13, 066 more per patient in the 60 d before AMR diagnosis and 35, 740 per patient per year higher in the 2 years after AMR diagnosis. Conclusions: US kidney transplant recipients with AMR have substantially greater healthcare utilization and higher costs and risk of graft loss and mortality.